Soil Fertility Status as Influenced by Slope Gradient and Land Use Types in Southern Ethiopia - Kedir Merga; Gifole Gidago; Fanuel Laekemariam (Applied and Environmental Soil Science)
Understanding the effects of land use types and slope gradients on the physicochemical properties of soil is essential for sustainable soil management. Therefore, this study was conducted at the Azit subwatershed of Gedebano Gutazer Welene Woreda, Southern Ethiopia, with the objectives to evaluate the effect of land use types, examine the interaction of land use and slope gradient, and evaluate the effect of slope gradient on selected soil physicochemical properties. A total of 27 soil samples using a simple random sampling technique with randomized complete block design from 3 land use types (cultivated, eucalyptus, and grazing lands) ×3 slope gradients (upper 10–15%, middle 5–10%, and lower 2–5% slopes) ×3 replications and depth (0–20 cm) were collected. Results indicated that most of the physicochemical properties of soils were significantly (P<0.01) affected by land use and slope gradient. Silt and sand particles did not vary significantly (P>0.05) among the land use types. The interaction effect of land use and slope was not significant (P>0.05) for most of the soil properties except for organic carbon (OC). Results of data analysis also showed that soil fertility was low under cultivated and eucalyptus lands coupled with the upper slope gradient. Therefore, based on the study’s findings, it can be recommended that integrated soil fertility management practices, such as the addition of soil organic matter and appropriate use of inorganic fertilizers, need to be implemented to restore the lost soil fertility status on the cultivated land and ultimately increase agricultural productivity on a sustainable basis. Eucalyptus plantings should also gradually be replaced by those that assist the soil in restoring its fertility.